Inquiry-based learning: Development of an introductory manufacturing processes course based on a mobile inverted pendulum robot. Issue 4 (October 2020) - Ma, Junkun; Coogler, Keith; Suh, Minjae
This paper describes the development of an innovative introductory manufacturing processes course designed to expose students to a broad overview of fundamental concepts, methods, procedures, tools, and equipment used in the manufacturing industry. Based on an educational mobile inverted pendulum robot, students are introduced to product design and prototyping by identifying an existing problem with a component in the robot, redesigning the component using computer aided design software, and then building a prototype using additive manufacturing methods. Subsequently, a set of hypothetical design requirement changes is imposed, and various design methods and manufacturing processes that can be used to make components to satisfy these new requirements are discussed. Topics covered include integrated product design, additive manufacturing prototyping based on different technologies, plastic injection molding, sand casting, and fundamentals of both computer aided manufacturing and computer numerical control machining. Tools, fixtures, and accessories required in these processes, as well as associated challenges, are also discussed. This course adapts the inquiry-based learning active learning pedagogical approach and focuses on the development of students' ability to conduct analytical analysis and to apply a knowledge of mathematics, science, engineering, and technology to solve practical engineering technology problems. As an introductory course designed to be offered to freshman level students, this course engages students in engineering technology related topics and stimulates their interest in manufacturing related subjects. It helps with improving the engineering student retention rate and serves as a pathway connecting students to more advanced specialized manufacturing courses such as computer numerical control machining technology. This paper presents course materials developed and student feedback as well as their evaluation of the course effectiveness based on a summative questionnaire-style survey from the first cohort of students.